Recurrent ACPA-positive pericarditis, would it be a pre-clinical manifestation of RA? - Laila Hamri; Samira Rabhi (Sciendo, 2023)
Rheumatoid arthritis (RA) is a chronic inflammatory rheumatic disease with an autoimmune component that preferentially affects the small joints of the hands and feet. Extra-articular manifestations may be associated with it. These are rather long-term complications compared to the inaugural forms of the disease.